The regional development of the Romanian rural tourism sector - Adriana AnaMaria Davidescu; Vasile Alecsandru Strat; Raluca Mariana Grosu; Ion Daniel Zgură; Sorin Anagnoste (Amfiteatru Economic Journal, 2018)
In the present paper we put forward a clear assessment of the Romanian rural tourism, from a regional perspective. Based on data for 2016, using principal component analysis for mixed data and cluster analysis, we outline an accurate image of the Romanian rural tourism at NUTS level 3, focusing on its main determinants and key regional poles of development. The novelty of the paper lays in developing one of the first composite indices measuring the rural tourism sector, in the Romanian scientific literature, which allows to rank the counties based on their performance and in providing a mapping of rural tourism, highlighting the counties with promising potential for developing activities in this sector. With high practical value, our empirical results may represent an important starting point in developing coherent policies meant at supporting and promoting rural tourism which can become an important generator of wealth and growth in the rural areas of Romania.
Keywords: L83; O18; P25; P48; 330; regional development; rural tourism; principal component analysis (PCA); regional disparities; rural Romania